ABAC access control policy generation technique based on deep learning - Aodi LIU; Xuehui DU; Na WANG; Rui QIAO (Tongxin xuebao)
To solve the problem of automatic generation of access control policies, an access control policy generation framework based on deep learning was proposed.Access control policy based on attributes could be generated from natural language texts.This technology could significantly reduce the time cost of access control policy generation and provide effective support for the implementation of access control.The policy generation problem was decomposed into two core tasks, identification of access control policy sentence and access control attribute mining.Neural network models such as BiGRU-CNN-Attention and AM-BiLSTM-CRF were designed respectively to realize identification of access control policy sentence and access control attribute mining, so as to generate readable and executable access control policies.Experimental results show that the proposed method has better performance than the benchmark method.In particular, the average F1-score index can reach 0.941 in the identification task of access control policy sentence, which is 4.1% better than the current state-of-the-art method.